Ativa mente: jogo didático para ensino do componente curricular de educação física nos anos finais do ensino fundamental - Bessa, Priscila Bonora (2025)
Educational games have emerged as effective pedagogical tools, integrating playfulness into learning and engaging students interactively. Based on this, this study aimed to analyze the functionality and applicability of an educational game as a pedagogical tool for teaching thematic units in the Physical Education curriculum for the final years of Elementary School. The specific objectives were: a) To propose, as a final product, an educational game that integrates playful and educational elements serving as a pedagogical tool for teaching the following thematic units: dance, fighting, gymnastics, sports, adventure body practices, games and play; b) To identify students' perceptions about the applicability in relation to quality factors: usability and game experience; c) To test, adapt, and implement the game prototype in the classroom, evaluating its functionality, effectiveness, and comprehension by students. The research was characterized as a qualitative study employing action research. The sample consisted of 43 students from the 8th and 9th grades of Elementary School at Colégio Estadual do Campo Octávio Tozo, located in the city of Cascavel, Paraná. The data collection instrument used was the MEEGA+KIDS questionnaire, adapted to assess students' experience, perception of learning, and the game's relevance in the educational context. The educational game, Ativa Mente, was designed to engage students with questions related to the six thematic units of Physical Education. It incorporates various interactive elements to foster participation and enhance learning through playful activities. The results indicated that 85% of the students considered the Ativa Mente game easy to use, while 78% indicated that the game contributed to the understanding of Physical Education content. However, aspects such as the level of challenge and attention during the game showed room for improvement. The application of the game stimulated the active participation of the students, making learning more dynamic and meaningful. It is concluded that the Ativa Mente educational game is an effective pedagogical tool for teaching thematic units of Physical Education, promoting greater engagement and meaningful learning. The study contributes to the area of School Physical Education, highlighting the potential of innovative and playful practices in the teaching-learning process.